(untitled) (Nigerian Journal of Technology, 2018)
Preliminary sizing of the members of high-rise buildings for adaptation in Nigeria and other countries with similar earth tremor data is carried out in this work using the linear static (lateral force) method. The studied building model comprises a regular, symmetric 50 storey Steel Dual-Concentric (chevron) Brace Frame, SD-CBF. European wide flange beam section of HE220M, column section HE260M and brace section HE180B were realised as initial design sections which are structurally safe. Results indicate that the aforementioned sections, though structurally safe can be made more robust for greater safety by applying a factor of safety ranging from 1.25 to 1.5 depending on available investment and seismicity of the environment. This is to justify safety of lives and properties. http://dx.doi.org/10.4314/njt.v37i3.2